EFEK KURKUMIN DAN PENTAGAMAVUNON-0 TERHADAP VIABILITAS KULTUR SEL LUTEAL - Purwaningsih, Endang (Lembaga Penelitian Universitas YARSI, 2009)
The purpose of this study was to investigate the effect of curcumin and pentagamavunonn-0 (PGV-0) on the viability of cultured luteal cells (percent of viable cells). The cultured luteal cells were obtained from corpus luteum of induced 12 immature Sprague Dawley rats by a single 10 IU Pregnat Mare?s Serum Gonadotropin. Subject in this study was 4 days old corpus luteum which was cultured in Minimal Essential Medium (MEM) containing 10% Fetal Bovine Serum. This experiment consisted of 12 groups, e.g. one group as control (solvent), three groups as control with LH and or PGF2 stimulation, and eight groups treated with 100 ?M curcumin and PGV-0 in three replicates. Evaluation was conducted after 24 hours of treatment by observation of viable cells with MTT method. The result showed that the viability of cultured luteal cells with curcumin or PGV-0 only was not significantly different compared to control goups. However, curcumin and PGV-0 on cultured luteal cells stimulated by LH and or PGF2 showed significant differences compared to control or LH and PGF2 only.